Control charts as a tool for improving the quality of laboratory analyses - Đukić Miloš; Vasiljević Sanela; Adamović Dragana; Požega Emina (Bakar, 2025)
The validity of test results represents one of the most important aspects in the implementation of the SRPS ISO/IEC 17025 standard and is a key factor in the operation of accredited laboratories. Ensuring reliable results is achieved through continuous monitoring and analysis of the obtained data, using appropriate statistical methods. One of the most effective methods for this purpose is the use of control charts, which provide a visual representation of the analytical system's stability and quickly indicate deviations or the occurrence of significant changes in the process. The aim of this paper is to present the theoretical basis and application of various types of control charts (X, X-blank, R, r and D) in chemical analysis, with a special focus on their use in accredited laboratories.